A casein hydrolysate protects mice against high fat diet induced hyperglycemia by attenuating NLRP3 inflammasome‐mediated inflammation and improving insulin signaling. Issue 11 (8th September 2016) - Healy, Niamh P.; Kirwan, Anna M.; McArdle, Maeve A.; Holohan, Kieran; Nongonierma, Alice B.; Keane, Deirdre; Kelly, Stacey; Celkova, Lucia; Lyons, Claire L.; McGillicuddy, Fiona C; Finucane, Orla M; Murray, Brian A.; et al.
Abstract : A hydrolysate derived from bovine milk casein (CH) reduces levels of the active form of the proinflammatory cytokine IL‐1β by impeding both signal 1 (pro‐IL‐1β transcription) and signal 2 (caspase‐1 activation) of the NLRP3 inflammasome. This anti‐inflammatory effect translates into improved glucose tolerance in vivo. Abstract : Scope: Activation of the nod‐like receptor protein 3 (NLRP3) inflammasome is required for IL‐1β release and is a key component of obesity‐induced inflammation and insulin resistance. This study hypothesized that supplementation with a casein hydrolysate (CH) would attenuate NLRP3 inflammasome mediated IL‐1β secretion in adipose tissue (AT) and improve obesity‐induced insulin resistance. Methods and results: J774.2 macrophages were LPS primed (10 ng/mL) and stimulated with adenosine triphosphate (5 mM) to assess NLRP3 inflammasome activity. Pretreatment with CH (1 mg/mL; 48 h) reduced caspase‐1 activity and decreased IL‐1β secretion from J774.2 macrophages in vitro. 3T3‐L1 adipocytes cultured with conditioned media from CH‐pretreated J774.2 macrophages demonstrated increased phosphorylated (p)AKT expression and improved insulin sensitivity. C57BL/6JOLaHsd mice were fed chow or high fat diet (HFD) for 12 wk ± CH resuspended in water (0.5% w/v). CH supplementation improved glucose tolerance in HFD‐fed mice as determined by glucose tolerance test. CH supplementation increased insulin‐stimulated pAKT protein levels in AT, liver, and muscle after HFD. Cytokine secretion was measured from AT and isolated bone marrow macrophages cultured ex vivo. CH supplementation attenuated IL‐1β, tumor necrosis factor alpha (TNF‐α) and IL‐6 secretion from AT and IL‐1β, IL‐18, and TNF‐α from bone marrow macrophages following adenosine triphosphate stimulation ex vivo. Conclusion: This novel CH partially protects mice against obesity‐induced hyperglycemia coincident with attenuated IL‐1β secretion and improved insulin signaling.